Seed endophytes and rhizosphere microbiome of Imperata cylindrica, a pioneer plant of abandoned mine lands - Mao, Wenqin; Wu, Ying; Li, Qiaohong; Xiang, Yingying; Tang, Wenting; Hu, Haiyan; Ji, Xiuling; Li, Haiyan (Frontiers in Microbiology, 2024)
Some plant-associated microorganisms could improve host plants biotic and abiotic stress tolerance.Imperata cylindrica is a dominant pioneer plant in some abandoned mine lands with higher concentrations of heavy metal (HM). To discover the specific microbiome of I. cylindrica in this extreme environment and evaluate its role, the microbiome of I. cylindrica's seeds and rhizosphere soils from HM heavily contaminated (H) and lightly contaminated (L) sites were studied. It was found that HM-contamination significantly reduced the richness of endophytic bacteria in seeds, but increased the abundance of resistant species, such as Massilia sp. and Duganella sp.. Spearman's rank correlation coefficient analysis showed that both Massilia sp. and Duganella sp. showed a significant positive correlation with Zn concentration, indicating that it may have a strong tolerance to Zn. A comparison of the microbiome of rhizosphere soils (RS) and adjacent bare soils (BS) of site H showed that I. cylindrica colonization significantly increased the diversity of fungi in rhizosphere soil and the abundance of Ascomycota associated with soil nutrient cycling. Spearman's rank correlation coefficient analysis showed that Ascomycota was positively correlated with the total nitrogen.Combined with the fact that the total nitrogen content of RS was significantly higher than that of BS, we suppose that Ascomycota may enhance the nitrogen fixation of I. cylindrica, thereby promoting its growth in such an extreme environment. In conclusion, the concentration of HM and nutrient contents in the soil significantly affected the microbial community of rhizosphere soils and seeds of I. cylindrica, in turn, the different microbiomes further affected soil HM concentration and nutrient contents. The survival of I. cylindrica in HM severely contaminated environment may mainly be through recruiting more microorganisms that can enhance its nutrition supply.